Is reactivation of autophagy a possible therapeutic solution for obesity and metabolic syndrome? - Sciarretta, Sebastiano (Landes Bioscience, 2012)
The molecular mechanism regulating the cardiomyocyte response to energy stress has been a hot topic in cardiac research in recent years, since this mechanism could be targeted for treatment of patients with ischemic heart disease. We have shown recently that the activity of RAS homolog enriched in brain (RHEB), a small GTP binding protein, is inhibited in response to glucose deprivation (GD) in cardiomyocytes and ischemia in the mouse heart. This is a physiological adaptation, since it inhibits complex 1 of the mechanistic target of rapamycin (MTORC1) and activates autophagy, thereby promoting cell survival during GD and prolonged ischemia. Importantly, the physiological inhibition of RHEB-MTORC1 signaling during myocardial ischemia is impaired in the presence of obesity and metabolic syndrome caused by high-fat diet (HFD) feeding, leading to a dramatic increase in ischemic injury. Although MTORC1 and autophagy can be regulated through RHEB-independent mechanisms, such as the AMPK-dependent phosphorylation of RPTOR and ULK1, RHEB appears to be critical in the regulation of MTORC1 and autophagy during ischemia in cardiomyocytes, and its dysregulation is relevant to human disease. Here we discuss the biological relevance of the dysregulation of RHEB-MTORC1 signaling and the suppression of autophagy in obesity and metabolic syndrome.